ANALYZING THE CONCEPTUAL MODEL OF SERVICE QUALITY AND ITS RELATIONSHIP WITH GUESTS’ SATISFACTION: A STUDY OF HOTELS IN ERBIL - Anwar, Kofand (The International Journal of Accounting and Business Society, 2017)
Nowadays most industries used service quality in various field.  All industries are implementing five service quality dimensions; these dimensions are tangible, assurance, reliability, responsiveness, and empathy. The main aim of this research is to investigate hotels’ service quality and its affect on guests’ satisfaction in Erbil. Moreover, to find which service quality dimension has more affect than the other quality dimensions. The researcher utilized a quantitative research method to measure the relationship between each service quality dimension on guests’ satisfaction. A questionnaire was adapted and distributed on guests at hotels in Erbil. 111 questionnaires completed and received from hotel guests in Erbil. The findings showed that the responsive as service dimension had the highest value; on the other hand assurance as service dimension had the lowest value.